Aquaculture-aided aquatic restoration and conservation: Highlights, challenges, and key lessons from global case studies - Emilee D. Benjamin; Casey A. Murray; Ricardo Riquelme; Edward Camp; Andrew Jeffs; Joshua Patterson; Aaron Pilnick; Jennifer Gumm; Taylor Lipscomb; Gesica Aroca; Marcela Ávila; Holly Richards; et al. (Fisheries Research, 2026)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

From PDB files to protein features: a comparative analysis of PDB bind and STCRDAB datasets - Sarwan Ali; Prakash Chourasia; Murray Patterson (Medical & Biological Engineering & Computing, 2024)

ViralVectors: compact and scalable alignment-free virome feature generation - Sarwan Ali; Prakash Chourasia; Zahra Tayebi; Babatunde Bello; Murray Patterson (Medical & Biological Engineering & Computing, 2023)

Efficient analysis of COVID-19 clinical data using machine learning models - Sarwan Ali; Yijing Zhou; Murray Patterson (Medical & Biological Engineering & Computing, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

New Zealand estuary benthic health indicators summarised nationally and by estuary type - Anna Berthelsen; Javier Atalah; Dana Clark; Eric Goodwin; Jim Sinner; Murray Patterson (New Zealand Journal of Marine and Freshwater Research, 2020)
Ecological data are often collected at small geographic scales. However, analysing data collectively over wider scales can reveal results and patterns not shown in the smaller‐scale data. We summarised data for intertidal benthic ecological (physico‐chemical and biological) health indicators from New Zealand estuaries and compared the results against thresholds above which ecological impacts are expected to occur. Values for the sediment physico‐chemical indicators mud and nutrients (nitrogen and phosphorus collectively) were above thresholds for at least 50% and at 31% of sites measured respectively. Sediment organic content and metal concentrations were generally low, with only maximum values exceeding the thresholds. Scores for biological indicators were within (or better than) the moderate health category for either at least 50%, or at least 75%, of sites. When compared across estuary types (based on a geomorphic classification system) we found statistically significant differences for thirteen of the sixteen indicators. Differences (among mean values) for highly significant results were relatively large compared to the range of values observed nationally for those indicators. However, the differences, except those for mud, were smaller than their respective ecological health threshold values. Our summary provides a reference for future comparisons of estuary indicators nationally and across estuary types.

From frontier economics to an ecological economics of the oceans and coasts - Murray Patterson; Bruce Glavovic (Sustainability Science, 2013)

The complimentary role of genetic and ecological data in understanding population structure: a case study using moose (Alces alces) - L. A. Finnegan; P. J. Wilson; G. N. Price; S. J. Lowe; B. R. Patterson; M.-J. Fortin; D. L. Murray (European Journal of Wildlife Research, 2012)

Effects of caffeine on alertness as measured by infrared reflectance oculography - Natalie Michael; Murray Johns; Caroline Owen; John Patterson (Psychopharmacology, 2008)

Bridging the divide in urban sustainability: from human exemptionalism to the new ecological paradigm - Garry W. McDonald; Murray G. Patterson (Urban Ecosystems, 2007)

Bridging the divide in urban sustainability: from human exemptionalism to the new ecological paradigm - Garry W. McDonald; Murray G. Patterson (Urban Ecosystems, 2007)